Antagonism and Dissent: Tensions and Limits within the Media’s Construction of Politics in Venezuela - Sibrian, Nairbis (2013)
Politics in Venezuela have always revolved around a conflict between two opposing poles. With the election of Hugo Chavez in 1998 and the coup d’état that followed in 2002, this characteristic was redefined and deeply accentuated. Antagonism has cemented a strong popular identity in Venezuela, in which a clear difference is marked between “them” (the people) and “we” (the enemies of the people). This tendency has gained momentum during electoral processes and is especially evidenced in the media, which is where antagonism was construed as an agreement to obliterate other voices and nullify dissent as a political form. This article analyzes the limits within this political construction, which can be tracked down through the discourses emitted by the Venezuelan state-owned television.